2019
DOI: 10.1002/14651858.cd011420.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow urine lipoarabinomannan assay for detecting active tuberculosis in people living with HIV

Abstract: Background The lateral flow urine lipoarabinomannan (LF-LAM) assay Alere Determine™ TB LAM Ag is recommended by the World Health Organization (WHO) to help detect active tuberculosis in HIV-positive people with severe HIV disease. This review update asks the question, "does new evidence justify the use of LF-LAM in a broader group of people?", and is part of the WHO process for updating guidance on the use of LF-LAM. Objectives To assess the accuracy of LF-LAM for the diagnosis of active tuberculosis among HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 131 publications
5
107
1
1
Order By: Relevance
“…Among symptomatic participants with CD4 counts >200 cells/µL, pooled sensitivity and specificity were 16% (95% CI: 8-31%) and 94% (95% CI: 81-97%) [21]. Among symptomatic participants with CD4 counts ≤200 cells/µL, pooled sensitivity and specificity were 45% (95% CI: 31-61%) and 89% (95% CI: 77-94%) [21]. Among children, data were limited, but five prospective pediatric cohort studies found a pooled sensitivity of 47% (95% CI: 27-69%) and specificity of 82% (95% CI: 71-89%) [24].…”
Section: First-generation Lam Testsmentioning
confidence: 98%
See 3 more Smart Citations
“…Among symptomatic participants with CD4 counts >200 cells/µL, pooled sensitivity and specificity were 16% (95% CI: 8-31%) and 94% (95% CI: 81-97%) [21]. Among symptomatic participants with CD4 counts ≤200 cells/µL, pooled sensitivity and specificity were 45% (95% CI: 31-61%) and 89% (95% CI: 77-94%) [21]. Among children, data were limited, but five prospective pediatric cohort studies found a pooled sensitivity of 47% (95% CI: 27-69%) and specificity of 82% (95% CI: 71-89%) [24].…”
Section: First-generation Lam Testsmentioning
confidence: 98%
“…The AlereLAM test meets the operational characteristics of the WHO TPP for a biomarker-based, non-sputum TB test, but falls short on test accuracy (Table 1). In 2019, a meta-analysis by Bjerrum et al [21] compared pooled sensitivity and specificity against a microbiological reference standard (MRS), defined as a positive TB culture or TB nucleic acid amplification test (NAAT). When compared against an MRS, pooled sensitivity and specificity in HIV-positive adults were 42% (95% CI: 31-55%) and 91% (95% CI: 85-95%), respectively [21].…”
Section: First-generation Lam Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of urinary LF-LAM was the predictor with the best ability of creating pure groups (either with or without tuberculosis); classifying almost 25% of the study sample (75% of which were true positives) regardless of their CD4 cell count. The false positive rate of 25% is less than a recent Cochrane review, in which 33% of participants with tuberculosis symptoms had a false positive urinary LF-LAM result for microbiologically confirmed tuberculosis 32 . However, inappropriate exclusions (e.g.…”
Section: Discussionmentioning
confidence: 61%